Frequencies of localized acoustic modes in dependence on mutual relation of components of Au/V nanolayers - Aleksiejuk, Mikołaj (Archives of Acoustics, 2007)
The paper presents the study of frequencies of the acoustic localized modes in metallicAu/V nanolayers. On the basis of Rytov model describing acoustic wave propagation in periodiclayered medium and Djafari–Rouhani formula the frequencies of localized modes werenumerically calculated. Dependencies of localized modes frequencies were presented graphicallyas a function of $b/L$ nanolayer parameter ($b$ – thickness of Au sublayer, $L$ – thickness ofAu/V bilayer) for first and second phononic stop bands. Obtained experimentally frequenciesof localized modes for Au/V nanolayers were compared with calculated values. Accordancebetween experimental and theoretical results is satisfactory.